Efektivitas Penerapan Problem Based Learning (PBL) Berbasis Etnofisika dalam Meningkatkan Pemahaman Konsep pada Pembelajaran Kesetimbangan Benda Tegar di SMA Kartika XIX Bandung - Kikin Sakinah; Fitria Arifiyanti; Heni Rusnayati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Low conceptual understanding of rigid body equilibrium is a persistent challenge in high school physics education, frequently attributed to teacher-centered instructional approaches and the absence of contextually meaningful learning experiences. Although prior studies have explored Problem Based Learning (PBL) and local wisdom-based approaches in isolation, empirical evidence examining the integrated effectiveness of ethnophysics-based PBL—particularly through the traditional game of engklek—on this topic remains scarce. This study aimed to investigate the effectiveness of an ethnophysics-based PBL model in improving students' conceptual understanding of rigid body equilibrium and to examine their responses toward the model. A quasi-experimental design with a Non-equivalent Control Group was employed. The experimental class received ethnophysics-based PBL instruction, while the control class followed conventional PBL. Conceptual understanding was assessed using a reasoned multiple-choice test and analyzed through normalized gain (N-gain), independent samples t-test, and effect size (Cohen's d); student responses were analyzed descriptively. The experimental class achieved a mean N-gain of 0.661 (moderate category), significantly higher than the control class at 0.293 (low category), with a t-test significance value of 0.000 and an effect size of 1.858 (very large category). Student responses fell in the high category with a mean score of 3.90. These findings provide empirical evidence that the ethnophysics-based PBL model effectively enhances students' conceptual understanding of rigid body equilibrium and offers a promising, contextually grounded instructional alternative for secondary physics education.